The right to non-discrimination on the grounds of disability: the complex coexistence of national and supranational legislation and case law - Milios, Georgios (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The adoption of the Convention on the Rights of Persons with Disabilities (CRPD) has substantially changed the landscape in relation to the right to non-discrimination of persons with disabilities and has had a clear impact on the case law and legislation at international and national level. This impact is detected in the interpretation of key concepts such as the definition of disability and the forms of discrimination. It also extends to more cross-cutting issues such as the interpretive methodology that is followed by the different courts. Despite the efforts of legal systems to adapt to the text of the Convention, certain problems of compatibility between national and EU legislation and case law and the CRPD can still be observed. Thus, this article focuses on these problems, arguing that a different regulation of certain issues is necessary for the coherence in the legal system to be guaranteed and the rights of persons with disabilities to be more effectively protected.